Blockade of XCL1/Lymphotactin Ameliorates Severity of Periprosthetic Osteolysis Triggered by Polyethylene-Particles - Tian, Yuan; Terkawi, Mohamad Alaa; Onodera, Tomohiro; Alhasan, Hend; Matsumae, Gen; Takahashi, Daisuke; Hamasaki, Masanari; Ebata, Taku; Aly, Mahmoud Khamis; Kida, Hiroaki; Shimizu, Tomohiro; Uetsuki, Keita; et al. (Frontiers in Immunology, 2020)
Periprosthetic osteolysis induced by orthopedic implant-wear debris continues to be the leading cause of arthroplasty failure in majority of patients. Release of the wear debris results in a chronic local inflammatory response typified by the recruitment of immune cells, including macrophages. The cellular mediators derived from activated macrophages favor the osteoclast-bone resorbing activity resulting in bone loss at the site of implant and loosening of the prosthetic components. Emerging evidence suggests that chemokines and their receptors are involved in the progression of periprosthetic osteolysis associated with aseptic implant loosening. In the current study, we investigated the potential role of chemokine C-motif-ligand-1 (XCL1) in the pathogenesis of inflammatory osteolysis induced by wear particles. Expressions of XCL1 and its receptor XCR1 were evident in synovial fluids and tissues surrounding loosened hip-implants of patients undergoing revision total hip arthroplasty. Furthermore, murine calvarial osteolysis model induced by ultra-high molecular weight polyethylene (UHMWPE) particles was used to study the role of XCL1 in the development of inflammatory osteolysis. Mice received single injection of recombinant XCL1 onto the calvariae after implantation of particles exhibited significantly greater osteolytic lesions than the control mice. In contrast, blockade of XCL1 by neutralizing antibody significantly reduced bone erosion and the number of bone-resorbing mature osteoclasts induced by UHMWPE particles. In consistence with the results, transplantation of XCL1-soaked sponge onto calvariae caused osteolytic lesions coincident with excessive infiltration of inflammatory cells and osteoclasts. These results suggested that XCL1 might be involved in the development of periprosthetic osteolysis through promoting infiltration of inflammatory cells and bone resorbing-osteoclasts. Our further results demonstrated that supplementing recombinant XCL1 to cultured human monocytes stimulated with the receptor activator of nuclear factor kappa-Β ligand (RANKL) promoted osteoclastogenesis and the osteoclast-bone resorption activity. Moreover, recombinant XCL1 promoted the expression of inflammatory and osteoclastogenic factors, including IL-6, IL-8 and RANKL in human differentiated osteoblasts. Together, these results suggested the potential role of XCL1-XCR1 axis in the pathogenesis of periprosthetic osteolysis and aseptic loosening. Our data broaden our knowledge of the pathogenesis of aseptic prosthesis loosening and highlight a novel molecular target for therapeutic intervention.